2018
DOI: 10.1155/2018/4062431
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib-Induced Hypopigmentation in Pediatric Patient with Chronic Myeloid Leukemia: A Case Report and Review of the Literature

Abstract: Dasatinib is an oral second-generation multitarget tyrosine-kinase inhibitor (TKI) that is efficacious in treating imatinib-resistant chronic myeloid leukemia (CML) or intolerant cases. Noncutaneous adverse effects with dasatinib are well known in the literature, most commonly cytopenias and fluid retention, while pigmentary abnormalities have rarely been reported. We report the case of a 12-year-old male known case of CML, who presented to dermatology clinic approximately 2 years after initiating dasatinib tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Pigmentary changes have also been reported in children taking c-KIT inhibitors. 25,26 In a retrospective study evaluating imatinib for chronic lymphocytic leukemia (CLL) in 30 children, 60% developed skin hypopigmentation. 27 This AE may be expected given c-KIT's involvement in melanocyte development, migration, and survival and known association with pigmentary disorders such as piebaldism.…”
Section: Cellul Ar Targ E Tsmentioning
confidence: 99%
“…Pigmentary changes have also been reported in children taking c-KIT inhibitors. 25,26 In a retrospective study evaluating imatinib for chronic lymphocytic leukemia (CLL) in 30 children, 60% developed skin hypopigmentation. 27 This AE may be expected given c-KIT's involvement in melanocyte development, migration, and survival and known association with pigmentary disorders such as piebaldism.…”
Section: Cellul Ar Targ E Tsmentioning
confidence: 99%
“…Brazzelli et al 68 . and Alharbi et al 67 . described hypopigmentation of the skin associated with dasatinib.…”
Section: Resultsmentioning
confidence: 99%
“…In one case, a biopsy was performed that showed decreased melanocytes and decreased basal layer melanin pigmentation. 67 Oro-Ayude et al 71 reported KP-like rash with both dasatinib and nilotinib, with biopsy results consistent with KP. Finally, Karaatmaca et al 69 reported successful desensitization to dasatinib in patients who developed a delayed urticarial rash.…”
Section: Bcr-abl Kinase Inhibitorsmentioning
confidence: 99%
See 2 more Smart Citations